Antibacterial activity and toxicity assay of biosynthesized silver nanoparticles by neem [azadirachta indica] leaves extract / Nur Amira Sariman - Sariman, Nur Amira (2020)
Recently, the development of nanotechnology using biological sources has attracted a great deal of attention among scientists since it is safe for human therapeutic uses as well as the environment. Therefore, this study aims to identify and characterize the presence of silver nanoparticles (AgNPs) from Azadirachta indica using UV-Visible spectroscopy as well as determine the antibacterial and toxicity activities of biosynthesized AgNPs. The AgNPs was biosynthesized by mixing 10 mL of A. indica leaves extract and 6 mL of 1 mM AgNO3, and heated at 60°C. Then, these AgNPs were characterized by UV-Vis spectroscopy (200 – 1000 nm). For the determination of the antibacterial activity of AgNPs, the Kirby-Bauer disc diffusion technique was used against Pseudomonas aeruginosa and Bacillus subtilis. The AgNPs biosynthesized from A. indica leaves extract also was tested for its toxicity by using the brine shrimp (Artemia salina nauplii) as the test organism. Therefore, the result of this study was found that the colour changes from light yellow to dark brown indicated the formation of AgNPs after 20 minutes and the UV-Vis spectrum displayed the highest peak was in the range of 420 – 450 nm. For the antibacterial activity of AgNPs at 1000 μg/mL, the highest zone of inhibition exhibited by P. aeruginosa and B. subtilis was 12.67 mm and 12.33 mm diameter, respectively. The LC50 value of brine shrimp lethality assay for AgNPs was 5223.22 μg/mL revealed that the biosynthesized AgNPs were non-toxic as the LC50 was above 1000 μg/mL, based on Meyer’s toxicity index. Overall, A. indica leaves extract can be used efficiently as an alternative for the production of potential antibacterial and non-toxicity of AgNPs.